Comparability of a short food frequency questionnaire to assess diet quality: the DISCOVER study. (18th August 2017) - Dehghan, Mahshid; Ge, Yipeng; El Sheikh, Wala; Bawor, Monica; Rangarajan, Sumathy; Dennis, Brittany; Vair, Judith; Sholer, Heather; Hutchinson, Nichole; Iordan, Elizabeth; Mackie, Pam; Samaan, Zainab
Abstract: This study aims to assess comparability of a short food frequency questionnaire (SFFQ) used in the Determinants of Suicide: Conventional and Emergent Risk Study (DISCOVER Study) with a validated comprehensive FFQ (CFFQ). A total of 127 individuals completed SFFQ and CFFQ. Healthy eating was measured using Healthy Eating Score (HES). Estimated food intake and healthy eating assessed by SFFQ was compared with the CFFQ. For most food groups and HES, the highest Spearman's rank correlation coefficients between the two FFQs were r > .60. For macro-nutrients, the correlations exceeded 0.4. Cross-classification of quantile analysis showed that participants were classified between 46% and 81% into the exact same quantiles, while 10% or less were misclassified into opposite quantiles. The Bland–Altman plots showed an acceptable level of agreement between the two dietary measurement methods. The SFFQ can be used for Canadian with psychiatric disorders to rank them based on their dietary intake.